(5x+15)=(3x-3)

Simple and best practice solution for (5x+15)=(3x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+15)=(3x-3) equation:


Simplifying
(5x + 15) = (3x + -3)

Reorder the terms:
(15 + 5x) = (3x + -3)

Remove parenthesis around (15 + 5x)
15 + 5x = (3x + -3)

Reorder the terms:
15 + 5x = (-3 + 3x)

Remove parenthesis around (-3 + 3x)
15 + 5x = -3 + 3x

Solving
15 + 5x = -3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
15 + 5x + -3x = -3 + 3x + -3x

Combine like terms: 5x + -3x = 2x
15 + 2x = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
15 + 2x = -3 + 0
15 + 2x = -3

Add '-15' to each side of the equation.
15 + -15 + 2x = -3 + -15

Combine like terms: 15 + -15 = 0
0 + 2x = -3 + -15
2x = -3 + -15

Combine like terms: -3 + -15 = -18
2x = -18

Divide each side by '2'.
x = -9

Simplifying
x = -9

See similar equations:

| X-(5x-1/3)=8-(6/5) | | -2x+y=a | | 5x+7x-12=144 | | 7x^2+31x-38=0 | | x^2+x-0.01=0 | | 7x^2+3x+3x+4=-3x+5 | | 2x/-3x=2 | | 4x^2-2x=px^2+2x+3 | | 7x=8x-15 | | 6x-3=10x+5 | | (2x^2-7x+3)(2x^2-x+3)+8x^2=0 | | 5x=40+3 | | -16=-5+2(2-m) | | 2x=19/6 | | 204=2y+y | | 5(x+3)+x=4(x+5)+3 | | 2x+80-4x=50 | | x(x/3)=12 | | x(x/3) | | x*x/3 | | 9x+2(60)=7x+7(60) | | c=120+.65y | | (2a-3)(4a^2+6a+9)=0 | | 2y+5y(2-y)=3-5y | | x(3x)=8 | | x^2-6x+y=0 | | x^3-4x^2+5x+2=0 | | cos(4*x-(pi))=-0.5 | | -2-3x=4x | | 2x^2+mx-3=0 | | 3X-18=-4 | | 13-6(x-16)=-33 |

Equations solver categories